2014
DOI: 10.1103/physreve.89.032711
|View full text |Cite
|
Sign up to set email alerts
|

Length-dependent β-sheet growth mechanisms of polyalanine peptides in water and on hydrophobic surfaces

Abstract: Fibrillar assemblies by peptides are becoming one of the most promising nanomaterials due to their exceptional properties. The self-assembly of peptides into β sheets is a critical step in the fibrillization pathway. We investigated the length-dependent β-sheet growth mechanisms of polyalanine [poly(A)] peptides consisting of 6 to 24 alanines (A6 to A24) in water and on the hydrophobic surface, respectively, by molecular dynamics simulations. β-sheet growth behavior in water fits negative exponential growth mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…MD simulations are ideally suited for modeling intertwined processes and can probe detailed chemical and physical interactions occurring between biopolymers and surfaces . However, most simulations have focused on adsorption of short peptides onto hydrophobic surfaces . For example, MD simulations were used to investigate the adsorption and aggregation of short peptides (GA) 4 and (GV) 4 on a rough hydrophobic surface, where peptides aggregated into layered β‐sheet structures .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MD simulations are ideally suited for modeling intertwined processes and can probe detailed chemical and physical interactions occurring between biopolymers and surfaces . However, most simulations have focused on adsorption of short peptides onto hydrophobic surfaces . For example, MD simulations were used to investigate the adsorption and aggregation of short peptides (GA) 4 and (GV) 4 on a rough hydrophobic surface, where peptides aggregated into layered β‐sheet structures .…”
Section: Introductionmentioning
confidence: 99%
“…For example, MD simulations were used to investigate the adsorption and aggregation of short peptides (GA) 4 and (GV) 4 on a rough hydrophobic surface, where peptides aggregated into layered β‐sheet structures . Most recently, a study investigated adsorption of ten polyalanine peptides with up to 24 repeats onto a hydrophobic surface . These results indicated that a hydrophobic surface can accelerate β‐sheet growth by enhancing local concentration and reducing conformational entropy of a peptide sequence.…”
Section: Introductionmentioning
confidence: 99%
“…13,20−22 The Ala-, His-rich segment exhibits the strongest peptide−peptide interactions, which are pH dependent with intermolecular bonding promoting β-sheets. 23 For suckerin, His provides supplemental pH-dependent support. At low pHs, His can increase protein solubility and, when near neutral pH, His can deprotonate, imparting more aromatic character on its imidazole which can then facilitate π−π stacking.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Suckerin is a globular protein with alanine- (Ala, A), threonine- (Thr, T), and His-rich nanoconfined β-sheets in a Gly-, leucine- (Leu, L), and tyrosine- (Tyr, Y) rich amorphous phase (Figure ). , The Ala-, His-rich segment exhibits the strongest peptide–peptide interactions, which are pH dependent with intermolecular bonding promoting β-sheets . For suckerin, His provides supplemental pH-dependent support.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is implicated in the fouling and degradation of medical implants, 16 and may play a role in the fibrillation of proteins associated with degenerative brain diseases such as Alzhemier's. [17][18] Given the widespread applications of peptide and protein adsorption, it is desirable to understand the molecular processes involved in this phenomenon. All-atom molecular dynamics has been widely used to study preferred structures of adsorbed peptides, [19][20] and studies in recent years have succeeded in estimating the free energy of adsorption, [21][22][23] and proposing mechanisms for the peptide adsorption process.…”
Section: Introductionmentioning
confidence: 99%